Evaluation of Tax Audit Effectiveness Factors in Jakarta Regional Tax Office - Frita Melliniawati; Mulyono (Universitas Medan Area, 2023)
Tax audit emerges as a form of control conducted by the Directorate General of Taxes to test taxpayer compliance towards implementing the self-assessment system. According to deterrence theory, taxpayer compliance is highly dependent on cost-benefit analysis, whereby the benefits of complying outweigh the consequences of not complying. Therefore, conducting an effective tax audit is important to increase taxpayer compliance. This study aims to evaluate the causes of the declining tax audit effectiveness based on the Audit Coverage Ratio (ACR) trend in the North Jakarta Regional Tax Office in 2019-2021 by using seven determinant factors of tax audit effectiveness as benchmarks. These factors are then divided into five categories, namely Top Management Support (financial budget adequacy, supporting facilities availability, professional training adequacy), Tax Auditor (Tax Auditor personnel sufficiency and workload), Technology (information system adequacy), and Taxpayers (taxpayers’ cooperativeness). This study used a descriptive-qualitative method by employing document analysis, questionnaires, and interviews. The results point out several issues that have led to the decline in the tax audit effectiveness in the North Jakarta Regional Tax Office, such as inadequate supporting facilities, ineffective professional training, insufficient tax auditor personnel, and lack of integration and accessibility on the existing information systems.